Maternal hepatitis B and infant infection among pregnant women living with HIV in South Africa. Issue 2 (22nd May 2014) - Hoffmann, Christopher J; Mashabela, Fildah; Cohn, Silvia; Hoffmann, Jennifer D; Lala, Sanjay; Martinson, Neil A; Chaisson, Richard E
Abstract : Introduction: Globally, hepatitis B virus (HBV) infection is the leading cause of liver‐related mortality. Newborn vaccination, maternal antiviral therapy and administering hepatitis B immune globulin shortly after birth can greatly reduce the risk of perinatal and infant infection. However, evidence‐based policy regarding these interventions in Africa is hampered by gaps in knowledge of HBV epidemiology. We describe maternal chronic hepatitis B (CHB) prevalence and infant infection during the first year of life within a cohort of women living with HIV. Methods: We recruited and prospectively followed pregnant women living with HIV and their infants from prenatal clinics in an urban area of South Africa. Hepatitis B surface antigen, anti‐hepatitis B surface antibodies and HBV DNA were assessed in all women. Hepatitis B testing was also performed at 6 and 52 weeks for all infants born to mothers with either positive surface antigen or detectable HBV DNA. Results: We enrolled 189 women with a median age of 29 years and median CD4 count of 348 cells/mm 3 . Fourteen had a positive surface antigen (7.4%), of which six were positive for "e" antigen. An additional three had detectable HBV DNA without positive surface antigen. One infant developed CHB and three others had evidence of transmission based on positive HBV DNA assays. HBV vaccinations were delivered at six weeks of life to all infants. Conclusions: Our findings highlight the risk of peripartum HBV transmission in this setting. Approaches to reducing this transmission should be considered.